Sanitation of stainless steel and other food-preparation surfaces - Frank, Joseph F.; Chimielewski, Revis A. N. (Nickel Development Institute, 1997)
This book describes of effectiveness of sanitation with quaternary ammonium compound or chlorine on stainless steel and other domestic food-preparation surfaces.
"Reprinted from: Journal of food protection, Volume 60. No.1, January. 1997"
Keywords: Food handling.; Food service -- Sanitation.; elektronické knihy; electronic books